Synthesis and Biological Evaluation of Thiazolidin-4-ones - RAJEEVA, B.; PRAVEEN KUMAR, A.; SHANTAKUMAR, S.M. (Asian Journal of Chemistry, 2010)
A new series of 2-(1,3-benzothiazol-2-ylimino)-5-arylidene-1,3- thiazolidine-4-ones (4) were synthesized and evaluated for their antiinflammatory and analgesic activity. The 2-(1,3-benzothiazol-2-ylimino)- 5-arylidene-1,3-thiazolidine-4-one (4) were synthesized from 2-(1,3- benzothiazol-2-ylimino)-1,3-thiazolidin-4-one (3) upon treating with different substituted aryl aldehydes. The 2-(1,3-benzothiazol-2-ylimino)- 1,3-thiazolidin-4-one (3) was prepared by treating 2-chloroacetamido benzothiazole (2) with potassium thiocyanate, where as the compound 2 was prepared by treating 2-aminobenzothiazole with chloroacetyl chloride in benzene medium. The synthesized 2-(1,3-benzothiazol-2- ylimino)-5-aryl-1,3-thiazolidine-4-one (4a1-a10) were screened for antiinflammatory and analgesic activity. The tested compounds exhibited good antiinflammatory and analgesic activity as compared to standard drug.